Clays in natural and engineered barriers for radioactive waste confinement - Norris, S.; Bruno, J.; Cathelineau, Michel; Delage, P.; Fairhurst, Charles; Gaucher, E. C.; Höhn, E. H.; Kalinichev, A.; Lalieux, P.; Sellin, P. (The Geological Society, 2014)
This Special Publication contains 43 scientific studies presented at the 5th conference on 'Clays in natural and engineered barriers for radioactive waste confinement' held in Montpellier, France in 2012. The conference and this resulting volume cover all the aspects of clay characterization and behaviour considered at various temporal and spatial scales relevant to the confinement of radionuclides in clay, from basic phenomenological process descriptions to the global understanding of performance and safety at repository and geological scales. Special emphasis has been given to the modelling of processes occurring at the mineralogical level within the clay barriers. The papers in this Special Publication consider research into argillaceous media under the following topic areas: large-scale geological characterization; clay-based concept/large-scale experiments; hydrodynamical modelling; geochemistry; geomechanics; mass transfer/gas transfer; mass transfer mechanisms. The collection of different topics presented in this Special Publication demonstrates the diversity of geological repository research.
Keywords: Radioactive waste disposal in the ground.; Clay.; Clay minerals.; elektronické knihy; electronic books